Birth Weight Reference for Triples in Korea - Kim, Jeong Ho (The Korean Academy of Medical Sciences, 2010)
An estimation of the baseline value of birth weight depending on gestational age is helpful for reducing morbidity and mortality following the early diagnosis and treatment of intrauterine growth retardation. In Korea, there are established baseline values for singletons and twins. But no definite criteria exist for triplets yet. Given the above background, we obtained the baseline value of birth weight depending on the gestational age in triplets with a gestational age of 27-38 weeks using a raw data about birth records which had been obtained during a 10-yr period from 1998 to 2007. This baseline value was compared with those of singletons and twins. During the 10-yr period, the total number of newborns who were born between gestational age 27 and 38 was 1,330,822. Of these, the number of singletons, twins and triplets was 1,330,822, 90,245, and 840, respectively. A mean gestational age was 37.3±1.5 weeks, 36.0±2.0 weeks and 33.3±2.4 weeks in the corresponding order. A mean birth weight was 3,071±490 g, 2,414±455 g, and 1,836±454 g in the corresponding order. A comparison of the birth weight depending on the gestational age of triplets was made with the normal value of singletons and twins. According to this, in the overall gestational age ranging from weeks 27 to 38, it was relatively smaller as compared with the birth weight of twins and singletons. The current study was of significance in that it first obtained the normal value of birth weight of triplets in the overall gestational age ranging from weeks 27 to 38, whose results are expected to be helpful for studies or treatments of triplets.